A Short Report on Megaliths and Petroglyphs on Natural Rock Surfaces from Farkawn and Khankawn Villages, Champhai District, Mizoram, India. (10th January 2017) - Lalhminghlua, .; Sarkar, Amrita
Megalithic tradition which is a worldwide phenomenon has been practiced by the Mizo society in the North-eastern part of India till recently. Expressions of thoughts and memories were incised on the megaliths. It is a significant feature through which the early history of the Mizo society can be reconstructed. This article tries to highlight the various megaliths found in the villages of Farkawn and Khankawn, their associated folklores and features. It also attempts to draw attention to the fact that besides building megaliths in memory of deceased people it was also a medium for expressing individual human experiences and emotions of the Mizo society.